2002
DOI: 10.1021/ac0204045
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as Pseudostationary Phase in Capillary Electrochromatography/ESI-MS

Abstract: A novel technique that uses polymer nanoparticles as pseudostationary phase in capillary electrochromatography with electrospray ionization mass spectrometry detection is described. A continuous full filling technique in which the nanoparticles were suspended in the entire electrolyte volume as well as a conventional partial filling technique is presented. No nanoparticles entered the mass spectrometer, which was fitted with an orthogonal electrospray interface, despite the continuous flow of nanoparticles int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
77
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 29 publications
2
77
2
Order By: Relevance
“…In 2002, Viberg et al [23] showed that it was possible to couple nanoparticle PSP-based CEC to ESI-MS with maintained ionization efficiency in absence of disturbing background signals and ion source contamination [24][25][26]. The technique was named continuous full filling (CFF), to distinguish it from PF that had previously been the only general technique available for coupling of PSP-based separations with ESI-MS detection (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Viberg et al [23] showed that it was possible to couple nanoparticle PSP-based CEC to ESI-MS with maintained ionization efficiency in absence of disturbing background signals and ion source contamination [24][25][26]. The technique was named continuous full filling (CFF), to distinguish it from PF that had previously been the only general technique available for coupling of PSP-based separations with ESI-MS detection (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 NPs were also used in electrophoresis techniques, either as modifiers to the wall of capillary or microchip, [9][10][11][12] or as pseudostationary phases (PSPs) in which they were added into the running buffers. [13][14][15] NPs used as PSPs can be replaced from run to run, and the stationary carry-over effects are thus avoided, favoring sample analysis in complex matrices. 16 Since the first report by Wallingford and Ewing, 17 various NPs to date have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…15 Viberg et al reported that the NPs in the buffer did not enter the mass spectrometer connected to the capillary via orthogonal electrospray interface, and the analytes were detected with high sensitivity. 13 The same research group employed NPs as PSPs in separation of neutral compounds, and they reported plate numbers as high as 700000/m. 14 Chang's group employed gold nanoparticles (GNPs) as additives in CE separation of DNA fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Gold NPs which are easily prepared were separately added to aqueous electrolytes and poly (ethylene oxide) solutions to optimize resolution for small solutes, as well as DNA and proteins [24][25][26][27][28][29][30][31]. Continuous filling and partial filling of polymeric NPs that serve as pseudostationary phases are both useful for the separations of three amines by CEC, without conducting time-consuming particle packing and using retaining frits [32].…”
Section: Introductionmentioning
confidence: 99%